If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2/3)x+(1/6)=(-5/6)x+(5/3)
We simplify the equation to the form, which is simple to understand
(2/3)x+(1/6)=(-5/6)x+(5/3)
Reorder the terms in parentheses
( + 0.66666666666667x)+( + 0.16666666666667)=(-0.83333333333333)*x+(+1.6666666666667)
Remove unnecessary parentheses
+ 0.66666666666667x+( + 0.16666666666667)=(-0.83333333333333)*x+(+1.6666666666667)
Remove unnecessary parentheses
+ 0.66666666666667x + 0.16666666666667=+(-0.83333333333333+)+*x+(+1.6666666666667+)
Reorder the terms in parentheses
+ 0.66666666666667x + 0.16666666666667=(-0.83333333333333x)+(+1.6666666666667)
Remove unnecessary parentheses
+ 0.66666666666667x + 0.16666666666667=-0.83333333333333x+(+1.6666666666667)
Remove unnecessary parentheses
+ 0.66666666666667x + 0.16666666666667=-0.83333333333333x+1.6666666666667
We move all terms containing x to the left and all other terms to the right.
+ 0.66666666666667x + 0.83333333333333x=+1.6666666666667-0.16666666666667
We simplify left and right side of the equation.
+1.5x=+1.5
We divide both sides of the equation by 1.5 to get x.
x=1
| 4x+12=3(x+4) | | -56=-4x-2(-7x-2) | | 7(6+x)=6(2-x) | | 328=8(6a+5) | | -5x=-x-12 | | 10x^2-66x+72=0 | | -4x+83=-12x-125 | | 0.5y-2=-.25 | | 10+5(x-2)=4x+1 | | -29=5x-2(3x+10) | | 36x+24=10(x+2+2x) | | 7h-14=42 | | -4-3=0.4x-2y | | -4(x+4)=2(x-10) | | 5g+15=42 | | 314=-x+576 | | -4-3=0.4-2y | | 2(4x+6)=-13+1 | | 3(3z-1)-3(3-2Z)=12 | | x+1=-x+3 | | 19+2(2n-15)=1 | | -4=-3x+5(-x+12) | | Ln(x-4)+ln(x-1)=ln(x-8) | | lnx=-10 | | 2[x+5(6-x)+18]-10=50-10x | | 28=t+24 | | -8(-8+2p)=192 | | 3x-x+6x=17 | | 12c-4=-12c | | 12-5x=6(x+2) | | 3.4k=7.82 | | 2q-5=11 |